2019
DOI: 10.18332/tid/105913
|View full text |Cite
|
Sign up to set email alerts
|

The effect of smoking on caries-related microorganisms

Abstract: INTRODUCTION Epidemiological studies have shown a close relationship between smoking and dental caries. Bacteria are one of the essential factors of caries formation. The imbalance of cariogenic bacteria and commensal bacteria in dental plaque results in higher production of acid that can corrode dental hard tissue. The aim of our review is to summarize the effect of smoking on caries-related bacteria. METHODS English articles available in Pubmed and ScienceDirect datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
40
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 71 publications
(102 reference statements)
4
40
0
1
Order By: Relevance
“…Similar results were observed in different studies [30][31][32] while results reported by Bregstrome et al are inconsistent with this study, in that study calculus load increased with increasing smoking exposure 33 . Moreover, missing teeth and dental caries frequency in this study shows a positive relation with smoking and results are consistent with other studies [34][35][36][37] .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Similar results were observed in different studies [30][31][32] while results reported by Bregstrome et al are inconsistent with this study, in that study calculus load increased with increasing smoking exposure 33 . Moreover, missing teeth and dental caries frequency in this study shows a positive relation with smoking and results are consistent with other studies [34][35][36][37] .…”
Section: Discussionsupporting
confidence: 93%
“…Smoking play a vital role in dental caries 36 and this study demonstrates a significant relation of smoking with dental caries and a meta-analysis is consistent with this study which revealed that ten out of eleven studies indicated a positive association between tobacco smoking and dental caries 35 . The results of this study also concludedthat calculus status plays a significantcorrelation with dental caries but study by Keyes et al reported that calculus is not responsible for dental caries 43 .…”
Section: Discussionsupporting
confidence: 87%
“…The bacterial composition of plaque (microbial homeostasis) remains relatively stable despite exposure to some environmental perturbations, such as smoking, high frequency sugar diet or diabetes (30)(31). Furthermore, smoking promotes the formation of a caries-susceptible environment by in uencing saliva buffer capability, changing its chemical agent and bacterial composition (32). As a result, dental plaque could be a predisposing factor for gingival diseases and dental caries if their microenvironment is perturbed (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…C. albicans strains increase their virulence when exposed to cigarette smoke. [34,35] Moreover, animal model experimentations have shown that long exposure to cigarettes attenuates the protection of the epithelium of the oral mucosa against C. albicans as evidenced by inflammation. [36] This study shows that the strains in general presented high hemolytic and Pz activities.…”
Section: Discussionmentioning
confidence: 99%